The Fats of Life : Essential Fatty Acids in Health and Disease - Lawrence, Glen D., 1948- (Rutgers University Press, 2010)
The Fats of Life delineates the importance of essential fatty acids, with a focus on distinctions between omega-3 and omega-6 fatty acid variants. The chemical and biochemical characteristics of these fatty acids and their metabolism to a vast array of potent bioactive messengers are described in the context of their potential effects on general health and impact on various diseases and neurological disorders.